Solution dynamics of the natural bioactive molecule capsaicin: a relaxation study. Issue 1 (2nd January 2019) - Bonechi, Claudia; Donati, Alessandro; Tamasi, Gabriella; Pardini, Alessio; Leone, Gemma; Consumi, Marco; Magnani, Agnese; Rossi, Claudio
Abstract: Nuclear magnetic resonance spectroscopy is a straightforward technique for studying molecular dynamics that range in timescale from picosecond (motions faster than molecular reorientation) to those that occur in real-time. This approach is important to highlight the behavior of bioactive molecules in solution, and to acquire information about action mechanisms and potential pharmacological effects. Proton and carbon-13 spin–lattice relaxation experiments were performed to calculate the reorientational correlation time for protonated carbons. Capsaicin showed complex dynamical properties and the results revealed two regions with different dynamical properties: the aliphatic region with fast reorientation motions and the aromatic region with slow motions.